Perceptions of Preparers and Users of Financial Statement on Disclosures of Research And Development Cost. Percepsi Penyedia dan Pemakai Laporan Keuangan Terhadapengungkapan Biaya Riset dan Pengembangan. - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThe main purpose of this study is to examine the cost and benefit on disclosures of the research and development (R&D) cost in a comparative study of the perceptions of financial managers (prepares of financial statement) and financial analysts (users of financial statement). Stated hypotheses to examine: first, differences of the perceived net cost or net benefit of disclosing research and development expenditure both mandatory disclosures or voluntary disclosures. Second, perceptions differences of number costs/disadvantages which constrain disclosures of R&D cost. Data collection was carried out by a questionnaire survey. Respondents included financial managers from manufacturing firms and financial analysts from securities houses. A series of t-tests was carried out to test the stated hypotheses. The results suggest that financial managers and financial analysts generally perceive disclosure of research and development (R&D) cost items resulting net benefit. It means that benefit of these disclosures, both mandatory or voluntary outweigh costs or disadvantage. The method is used to test the stated hypotheses is t test. The results show that first, there are no significant differences in the perceptions of financial managers and financials analysts about net benefit or net cost of disclosing research and development (R&D) cost items both mandatory or voluntary. Second, there are significant differences in the perceptions of financial managers and financials analysts about the magnitude of collecting and processing cost and auditing cost.